P3ht‐Graphene Device for the Restoration of Visual Properties in a Rat Model of Retinitis Pigmentosa. Issue 6 (23rd December 2022) - Francia, Simona; Di Marco, Stefano; DiFrancesco, Mattia L.; Ferrari, Davide V.; Shmal, Dmytro; Cavalli, Alessio; Pertile, Grazia; Attanasio, Marcella; Maya‐Vetencourt, José Fernando; Manfredi, Giovanni; Lanzani, Guglielmo; Benfenati, Fabio; et al.
Abstract: Retinal degeneration is one of the prevalent causes of blindness worldwide, for which no effective treatment has yet been identified. Inorganic photovoltaic devices have been investigated for visual restoration in advanced stage Retinitis pigmentosa (RP), although lack of implant flexibility and foreign‐object reactions have limited their application. Organic photoactive retinal prostheses may overcome these limitations, being biomimetic and tissue friendly. Inspired by organic photovoltaic strategies involving graphene, a hybrid retinal prosthesis is recently engineered consisting of a dual poly‐3‐hexylthiophene (P3HT) and graphene layer onto a flexible substrate. Here, this hybrid prosthesis is subretinally implanted in vivo in 5‐month‐old Royal College of Surgeons (RCS) rats, a rodent model of RP. Implanted dystrophic rats restored visual performances at both subcortical and cortical levels in response to light stimuli, in the absence of marked inflammatory responses. Moreover, the analysis of the physical‐mechanical properties after prolonged permanence in the eye showed excellent biocompatibility and robustness of the device. Overall, the results demonstrate that graphene‐enhanced organic photovoltaic devices can be suitably employed for the rescue of retinal dystrophies and supports the translation of the organic strategy into medical practice. Abstract : Inspired by organic photovoltaic, a hybrid retinal prosthesis consisting of poly‐3‐hexylthiophene (P3HT) and graphene on a flexible substrate is subretinally implanted in vivo in Royal College of Surgeons (RCS) rats, a model of Retinitis pigmentosa . Implanted dystrophic rats restored visual performances at both subcortical and cortical levels in response to light stimuli, in the absence of marked inflammatory responses.